P POTENSI EKSTRAK DAUN KETEPENG CINA (CASSIA ALATA L.) TERHADAP PENURUNAN KOLESTEROL DARAH MENCIT JANTAN HIPERLIPIDEMIA - Nadia Nadia Chitania; Tuti Alawiyah; Alifira Adhany Yustian; Maria Dwi Ayu Listiawati (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
Background: Cholesterol is an essential material to synthesize important substances in the body. Cholesterol is transported to various body tissues with the help of lipoprotein, which contain particles of fats, proteins and other substances. Hyperlipidemia is an increased level of lipids in the blood. Increased cholesterol levels occur mainly because of bad lifestyle; the habit of eating fast food or instant food which increasing cholesterol levels in the blood. Non-pharmacogical managements can be given by administering extracts of natural ingredients such as flavonoids contained in Ketepeng Cina.   Objective: To know the potential of ethanolic extract Ketepeng CinaLeaves to reduce plasma cholesterol in hyperlipidemic male mice.   Methods:Analyzing through the database, Pubmed, Google Scholar from 2010 to 2020 with the keyword of Chinese patty, and flavonoids.   Results:3 database search methods found 205 articles consisting of 24 google scholar, pubmed 169, and obtained 9 articles that filled the inclusion and exclusion criteria.Conclusion:The Potential Of Ethanolic Extract Ketepeng Cina Leaves (Cassia Alata L.)is proven To Contain Flavonoids That Can Reduce High Number Of Cholesterol Values In The Blood Of Test Animals Such As Mice.Keywords: Ketepeng Cina, Cassia alata L,Flavonoid, Hiperlipidemia, Cholesterol